A Newly Identified Islamic Text from Sixteenth-Century Java: A Guide to Islamic Prayer and Belief - Wayan Jarrah Sastrawan; Ali Yunis Aldahesh; Adrian Vickers (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2026)
Indonesia is a major part of the Islamic world and today contains the largest population of Muslims in a single nation-state. However, we still have a very limited understanding of how Islam became the archipelago’s predominant religion in the early modern period, because of the extreme paucity of local sources that bear witness to this process. This article investigates, for the first time, a recently identified bark-paper manuscript from sixteenth-century Java that sheds new light on the Islamization of Indonesia: a manuscript with shelf mark Ba 7 held in the Fulda Public Library in Germany. This unique text, to which we assign the title A Guide to Islamic Prayer and Belief, contains an introduction to the basic ideas and expressions of Islamic religion for a Javanese audience. As one of only seven Islamic texts known to have survived from this obscure period of Javanese history, the Guide illuminates significant aspects of early Indonesian Islam: the transmission of canonical Islamic texts to the archipelago, the assimilation of Arabic vocabulary into local languages, and the role of Islamic religious education in the region. This major new source prompts us to reconsider certain prevailing theories about the Islamization of Indonesia and points to exciting avenues for future research.